The low volatility anomaly in Chinese equity market - Hong, Zhuoling (2023)
The most well-known anomaly in finance suggests that there is no trade- off between risk and return. The portfolio of the low volatility stocks provides better returns than the portfolio of the high volatility stocks. The existing literature offers numerous possible explanations for this anomaly. One of the studies from Bali, Cakici, and Whitelaw (2011) demonstrates that investors’ demand for lottery-like stocks is a significant driver of the low beta anomaly and in this research, they introduced a behaviour measure variable "MAX", which represents lottery characteristics. Hence, in this paper, we are going to follow Bali et al. (2011, 2017)'s research and use "MAX" to investigate the demand for lottery-type stocks in explanation of the presence this anomaly in Chinese equity market.